Nanocarrier-based Drug Delivery of Brinzolamide for Ocular Diseases: A Mini-review - Maurya, Rashmi; Vikal, Akash; Patel, Preeti; Narang, Raj Kumar; Das Kurmi, Balak (Current Nanomedicine, 2025)
Brinzolamide (BRZ) represents a significant advancement in glaucoma treatment as a topically active carbonic anhydrase inhibitor (CAI). It exhibits selectivity and potent inhibitory activity for carbonic anhydrase type II isozyme (CA-II), which is crucial in aqueous humor secretion. With excellent ocular bioavailability and a formulation optimized for physiologic pH, brinzolamide effectively lowers intraocular pressure by inhibiting CA-II in ciliary processes. Its superior ocular comfort profile enhances patient compliance. Preclinical evaluations confirm its specific CA inhibition without notable side effects, and its low systemic absorption minimizes systemic CA inhibition-related issues. BRZ's prolonged tissue half-life in the eye ensures sustained IOP reduction, supported by clinical trials demonstrating comparable efficacy with reduced dosing frequency. Challenges in ocular disease treatment arise from physiological, anatomical, and dynamic barriers hindering effective drug delivery to the eye. Nanocarriers, such as micelles, nanoparticles, liposomes, niosomes, and dendrimers, offer promising solutions by improving permeation, targeting specific sites, and overcoming the limitations of conventional forms. This review explores diverse nanomedicines, detailing their applications, advantages, and disadvantages in ophthalmic drug delivery. It also includes recent research findings for a comprehensive overview of the current landscape.
Keywords: nanocarriers